Assessing the impact of smoking cessation services on reducing health inequalities in England: observational study. Issue 6 (29th November 2007) - Bauld, Linda; Judge, Ken; Platt, Stephen
Abstract : Objective: NHS stop smoking services are expected to play a key part in achieving the infant mortality and life expectancy health inequality targets in England by reducing smoking prevalence in deprived areas. This paper assesses the extent to which services have made a contribution to reducing inequalities in smoking between 2003–4 and 2005–6. Methods: Synthetic estimates of baseline smoking prevalence data were compared with national monitoring data about the numbers of smokers in receipt of services and the proportion who self report quitting at four weeks. The social distribution of service recipients and quitters was compared with estimates of smoking prevalence to assess impact on inequalities. Comparisons were made between officially designated disadvantaged areas (the Spearhead Group) and others. Results: Short-term cessation rates were lower in disadvantaged areas (52.6%) than elsewhere (57.9%) (p<0.001), but the proportion of smokers being treated was higher (16.7% compared with 13.4%) (p<0.001). The net effect was that a higher proportion of smokers in the most disadvantaged areas reported success (8.8%) than in more advantaged areas (7.8%) (p<0.001). Using the evidence-based assumption that three-quarters of short-term quitters will relapse within one year, the absolute and relative rate gaps in smoking prevalence between Spearhead areas and others are estimated to fall by small but statistically significant amounts from 5.2 and 1.215 (CIs: 1.216 to 1.213) to 5.0 and 1.212 (CIs: 1.213 to 1.210) between 2003–4 and 2005–6. Conclusion: NHS stop smoking services have probably made a modest contribution to reducing inequalities in smoking prevalence. To achieve government targets, however, requires both the development of more innovative cessation interventions for the most addicted smokers and action to ensure that other aspects of tobacco control policy make a larger contribution to inequality goals.